2017
DOI: 10.1080/16549716.2017.1387411
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a multi-sectoral response to HIV: a case study of AIDS councils in the Mpumalanga Province, South Africa

Abstract: Background: A multi-sectoral response is advocated by international organisations as a good strategy to address the multiple drivers and impact of human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS), and was historically mandated as a condition of funding. In March 2017, the South African National AIDS Council (SANAC) launched the latest 5 year National Strategic Plan (NSP) to address HIV, sexually transmitted infections and tuberculosis. As with previous iterations, the NSP calls for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Respondents in KIIs alluded to the difficulty of measuring impact of programmes when multiple actors are involved, which they understood to be one of the factors that explains poor collaboration in HIV programmes. We also found that lack of participation by some government departments in platforms that are meant to create space for collaboration between departments, renders these forums ineffective, as was observed elsewhere (Mahlangu, Vearey, Thomas, & Goudge, 2017).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Respondents in KIIs alluded to the difficulty of measuring impact of programmes when multiple actors are involved, which they understood to be one of the factors that explains poor collaboration in HIV programmes. We also found that lack of participation by some government departments in platforms that are meant to create space for collaboration between departments, renders these forums ineffective, as was observed elsewhere (Mahlangu, Vearey, Thomas, & Goudge, 2017).…”
Section: Discussionsupporting
confidence: 64%
“…This paper focuses on mainstreaming of HIV in the public sector in South Africa. Involvement, of civil society and the private sector in the multisectoral response to HIV in South Africa is reported elsewhere (Mahlangu, Vearey, Thomas, & Goudge, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study highlighted that these structures experience challenges in implementing a multisector approach. Detailed methods and full presentation of findings are discussed elsewhere [35,36]. Tables 1 and 2 presents a summary of the challenges.…”
Section: Multisector Collaboration On the Hiv Response In South Africamentioning
confidence: 99%
“…In regions with high HIV prevalence, proportions of sero-discordant intra-couple transmission range from 13.0 to 55% of new HIV infections [14]. For South Africa, the estimated proportion of sero-discordant couples is unclear, however, transmission among longer-term couples were estimated above 10.0% per year [15]. Thus the prevention of intra-couple HIV transmission may delay the progression of the epidemic.…”
Section: Definition and Prevalence Of Sero-discordance Globally Sadcmentioning
confidence: 99%
“…Since the start of the new millennium, the management of HIV was spearheaded by comprehensive, multi-sectorial action orientated National Strategic Plans for HIV/AIDS and Sexually Transmitted Infections [15]. Over the last 18 years, many gains have been made in curbing the HIV epidemic.…”
Section: Policies and Policy Implementationmentioning
confidence: 99%